New Onset of Dermatomyositis/Polymyositis during Anti-TNF-α Therapies: A Systematic Literature Review - Alexandra Maria Giovanna Brunasso; Werner Aberer; Cesare Massone (The Scientific World Journal)
We performed a systematic search of databases from 1990 to 2013 to identify articles concerning the new onset of dermatomyositis/polymyositis (DM/PM) in patients treated with anti-TNF-α therapy. We retrieved 13 publications describing 20 patients where the new onset of DM/PM after anti-TNF-α therapy was recorded. 17 patients were affected by rheumatoid arthritis (RA), one by Crohn’s disease, one by ankylosing spondilytis, and one by seronegative arthritis. In 91% of the cases antinuclear autoantibodies were detected after the introduction of anti-TNF-α therapy. In 6 patients antisynthetase antibodies were detected and other clinical findings as interstitial lung disease (ILD) were recorded. Improvement of DM/PM after anti-TNF suspension (with the concomitant use of other immunosuppressors) was recorded in 94% of cases. The emergence of DM/PM and antisynthetase syndrome seem to be associated with the use of anti-TNF-α agents, especially in patients with chronic inflammatory diseases (mainly RA) with positive autoantibodies before therapy initiation. In particular, physicians should pay attention to patients affected by RA with positive antisynthetase antibodies and/or history of ILD. In those cases, the use of the TNF-α blocking agents may trigger the onset of PM/DM or antisynthetase syndrome or may aggravate/trigger the lung disease.